Vergi suç ve cezaları - Çatalkaya, İbrahim Ekrem (My University, 2025)
“Vergi Suç ve Cezaları” adlı bu çalışma ile; 213 Sayılı Vergi Usul Kanunu’nda (VUK) düzenlenen ve müeyyidesine adli mercilerce karar verilen; Kaçakçılık Suçları, Vergi Mahremiyetinin İhlali Suçu ve Mükelleflerin Özel İşlerini Yapma Suçlarının çerçevesinin tespiti, ayrıntılı olarak ele alınması, Türk Ceza Kanunu ile örtüştüğü ve ayrıştığı noktaların ortaya konulması açısından genel suç teorisi kapsamında unsurları incelenmiş ve kanunun tatbikinde karşılaşılabilecek sorunlara ve çözüm yollarına katkıda bulunulmaya çalışılmıştır. Çalışmamızda öğretinin mevzulara yaklaşımı ve Yargıtay uygulamalarının ne şekilde olduğu derinlemesine ele alınıp kanun maddeleri detaylanmasına incelenmeye ve açıklanmaya çalışılmıştır. Öncelikle, 213 Sayılı VUK’ta müeyyideye bağlanan eylemler ve bu eylemlerin kabahat ve suç oluşturmalarına göre farklı usul ve yöntemle yaptırıma tabi olduğu hususları tümden gelim yöntemiyle genelden özele bir anlatımla ele alınmıştır.

With this study titled “Tax Crimes and Penalties,” the framework of Smuggling Crimes, Offence Against the Secrecy of Taxes, and Crimes of Conducting the Private Business of Taxpayers, which are regulated in the Tax Procedure Law (VUK) No. 213 and whose sanctions are determined by judicial authorities, has been examined in detail, and within the scope of the general theory of crime, their components have been analyzed in terms of identifying the points that coincide with and differ from the Turkish Penal Code, and efforts have been made to contribute to the problems and solutions that may be encountered in the implementation of the law. In our study, the approach of the doctrine to the issues and the manner in which the Court of Cassation practices have been addressed were examined in depth, and the provisions of the law were analyzed and explained in detail. First of all, the acts subject to sanctions under the Tax Procedure Law No. 213, and the fact that these acts are subject to sanctions through different procedures and methods depending on whether they constitute misdemeanours or crimes, have been discussed from the general to the specific by means of the deductive method.
Keywords: 213 Sayılı Vergi Usul Kanunu’nda Düzenlenen Vergi Suçları; Commercial crimes; Kaçakçılık Suçları; Law and legislation; Offence Against the Secrecy of Taxes and the Crimes of Conducting the Private Business of Taxpayers; Smuggling Crimes; Tax Crimes Enacted in the Tax Procedure Law Numbered 213; Tax evasion; Taxation; Ticari suçlar; Turkey; Türkiye; Vergi kaçakçılığı; Vergi Mahremiyetinin İhlali Suçu ve Mükelleflerin Özel İşlerini Yapma Suçu; Vergilendirme; Yasa ve yasama